2019
DOI: 10.1177/2047487319877268
|View full text |Cite
|
Sign up to set email alerts
|

Workload-indexed blood pressure response is superior to peak systolic blood pressure in predicting all-cause mortality

Abstract: Aims The association between peak systolic blood pressure (SBP) during exercise testing and outcome remains controversial, possibly due to the confounding effect of external workload (metabolic equivalents of task (METs)) on peak SBP as well as on survival. Indexing the increase in SBP to the increase in workload (SBP/MET-slope) could provide a more clinically relevant measure of the SBP response to exercise. We aimed to characterize the SBP/MET-slope in a large cohort referred for clinical exercise testing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 36 publications
3
63
2
Order By: Relevance
“…In addition, recent data suggest that using workloadindexed SBP response to exercise is superior to peak SBP in predicting mortality. 21 Earlier studies have found either increased 1,2,4 or decreased 7-9 risk of cardiovascular disease or death with higher peak SBP, in different populations. This can possibly be explained by the confounding effect of maximum workload (exercise capacity), associated both with higher SBP (via greater cardiac output) 12,14,15 and with better survival.…”
Section: Rationale For Using Workload-indexed Sbp Measuresmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, recent data suggest that using workloadindexed SBP response to exercise is superior to peak SBP in predicting mortality. 21 Earlier studies have found either increased 1,2,4 or decreased 7-9 risk of cardiovascular disease or death with higher peak SBP, in different populations. This can possibly be explained by the confounding effect of maximum workload (exercise capacity), associated both with higher SBP (via greater cardiac output) 12,14,15 and with better survival.…”
Section: Rationale For Using Workload-indexed Sbp Measuresmentioning
confidence: 96%
“…The workload-indexed SBP response to exercise has been proposed as a more physiologically relevant metric than peak SBP, 11 and current guidelines on hypertension management 10 as well as exercise testing recommendations 16,17 highlight the importance of considering workload when interpreting SBP during exercise. However, while reference values on peak SBP are available, [18][19][20] normative data for the workloadindexed SBP response to exercise testing are scarce 21 and, to our knowledge, non-existing for females and for bicycle ergometry. Thus, the current results fill an important gap in the literature and may aid physicians and exercise physiologists in interpretation of the SBP response during clinical bicycle exercise testing.…”
Section: Rationale For Using Workload-indexed Sbp Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that this may be related to a better distinction in identifying Korotkoff sounds in higher (systolic) BPs, making them louder for auscultation. Detailed information, though, on the BP measurement devices and techniques used in the study by Hedman et al 6 were not provided, challenging the reproducibility of the findings. Despite the added prognostic precision provided by the findings that a higher SBP/MET slope was associated with worse survival, the underlying cause for this association remains elusive.…”
mentioning
confidence: 99%
“…7 Exaggerated SBP response to exercise has also been demonstrated to be associated with an increased risk of sudden cardiac death in men without a history of CVD compared with those with normal SBP response to exercise testing (HR 1.73, 95% CI 1.07-2.82). 11 The results of a recently published study 12 including a large cohort of male subjects (N ¼ 7298; 58.6 AE 11.0 years; follow-up 18.4 years) revealed a higher workload-indexed SBP response to exercise rather than a higher peak SBP to be predictive of all-cause mortality. Furthermore, the authors suggested it might be time to rethink the threshold of 'normal' SBP response to progressive exercise.…”
mentioning
confidence: 99%